The impacts of the COVID-19 pandemic on birth satisfaction and birth experiences in Russian women - Suarez, Anna; Yakupova, Vera (Frontiers in Global Women's Health, 2022)
Background Women's satisfaction with their childbirth experiences has significant impacts on their health and the health of their children. Recently, childbirth and maternity care systems have been disrupted by the COVID-19 pandemic. This study aimed to investigate the association of birth satisfaction with mode of birth, medical interventions, support during labour, type of childbirth healthcare plan and antenatal education in the context of the COVID-19 pandemic in Russia. Methods 1,645 Russian women who gave birth during the first year of the COVID-19 pandemic and 611 matched controls who gave birth in the previous year participated in an anonymous Internet survey about their childbirth experience. The survey included questions regarding women's demographic and obstetric characteristics as well as their childbirth experiences. Birth satisfaction was measured using the Birth Satisfaction Scale Revised Indicator (BSS-RI). Results Birth satisfaction scores did not show notable changes before and during the pandemic (Pearson Chi-square = 19.7, p = 0.22). Women had lower BSS-RI scores if they tested positive for COVID-19 during labour (F = 9.18, p = 0.002), but not during pregnancy or postpartum (p > 0.32). In both cohorts women who had vaginal births rated birth satisfaction higher than those who had caesarean births. The more medical interventions there were, the lower were the BSS-RI scores (B = −0.234, 95% CI: −0.760; −0.506, p < 0.001), but only during the pandemic. Birth satisfaction was higher if women had a support person present during labour (F > 7.44, p < 0.001), which was not possible for over 70% of participants during the pandemic. In both cohorts birth satisfaction was associated with the childbirth healthcare plan (F > 5.27, p < 0.001), but not with antenatal education (F < 0.15, p > 0.43). Conclusions Our study highlights the significant impacts of the COVID-19 pandemic on the birth experiences of Russian women. Sustaining the rights of women to informed decisions during labour, respect for their preferred childbirth healthcare plan, presence of the birth team of choice and professional support for home birth are essential for higher birth satisfaction and better health outcomes for mothers and their infants.